2015
DOI: 10.3389/fphar.2015.00179
|View full text |Cite
|
Sign up to set email alerts
|

Computational drug repositioning for peripheral arterial disease: prediction of anti-inflammatory and pro-angiogenic therapeutics

Abstract: Peripheral arterial disease (PAD) results from atherosclerosis that leads to blocked arteries and reduced blood flow, most commonly in the arteries of the legs. PAD clinical trials to induce angiogenesis to improve blood flow conducted in the last decade have not succeeded. We have recently constructed PADPIN, protein-protein interaction network (PIN) of PAD, and here we combine it with the drug-target relations to identify potential drug targets for PAD. Specifically, the proteins in the PADPIN were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“… Brian Annex, MD , was the principal investigator on an award made to University of Virginia to test an AstraZeneca drug (ZD5054 link to: ncats.nih.gov/files/ZD5054.pdf) in patients with peripheral artery disease. The trial used imaging as a noninvasive method to measure calf blood flow at rest and during exercise was used as a more objective and quantitatively reproducible POC end point compared to the traditionally used subjective and effort‐dependent 6‐min walk test measuring the distance traveled over a 6‐min period 14 . This was also shown to decrease POC study size and duration, thus, improving the likelihood of more frequent testing of novel agents (previously limited by study expense, subjectivity, and outcome variability) for this indication in the future. John Krystal, MD (link to: https://reporter.nih.gov/search/B9Xu1HDwMUKpl1maeyaAPg/project‐details/8913287) was the principal investigator on an award made to Yale University to test a Pfizer drug (PF‐03463275: link to ncats.nih.gov/files/PF‐03463275.pdf) in patients with schizophrenia.…”
Section: Use Casesmentioning
confidence: 99%
“… Brian Annex, MD , was the principal investigator on an award made to University of Virginia to test an AstraZeneca drug (ZD5054 link to: ncats.nih.gov/files/ZD5054.pdf) in patients with peripheral artery disease. The trial used imaging as a noninvasive method to measure calf blood flow at rest and during exercise was used as a more objective and quantitatively reproducible POC end point compared to the traditionally used subjective and effort‐dependent 6‐min walk test measuring the distance traveled over a 6‐min period 14 . This was also shown to decrease POC study size and duration, thus, improving the likelihood of more frequent testing of novel agents (previously limited by study expense, subjectivity, and outcome variability) for this indication in the future. John Krystal, MD (link to: https://reporter.nih.gov/search/B9Xu1HDwMUKpl1maeyaAPg/project‐details/8913287) was the principal investigator on an award made to Yale University to test a Pfizer drug (PF‐03463275: link to ncats.nih.gov/files/PF‐03463275.pdf) in patients with schizophrenia.…”
Section: Use Casesmentioning
confidence: 99%
“…By combining PADPIN with gene expression data collected from ischemic and nonischemic gastrocnemius muscles from two mouse strains (C57BL/6 and BALB/c) subjected to hindlimb ischemia (a commonly used experimental PAD mouse model), the authors identified a list of genes with potential therapeutic significance in PAD and demonstrated the feasibility of using such an omics‐based in silico platform for PAD research. Later, PADPIN was also combined with extensive drug‐target relationships derived from public drug databases to facilitate the identification of potential drug repositioning candidates for PAD from the aspect of promoting angiogenesis and alleviating inflammation (Chu, Annex, & Popel, 2015).…”
Section: Omics Data‐driven Systems Biology Studies Related To Angioge...mentioning
confidence: 99%
“…Only a limited number of genes are activated, and large amounts of proteins and peptides are produced after the transcription, translation, and post-translational modifications of these genes. The body has a complex protein network, which ensures that every cell, tissue, and organ achieves its biological function by adhering to the physiological laws (9,10). Therefore, proteomic analysis is an important part of modern bioinformatics.…”
Section: Proteomic Technologiesmentioning
confidence: 99%